Management of stormwater runoff from the perspective of ecosystem services. Analysis of its implementation in the main cities of Argentina - Zapperi, Paula Andrea; Montico, Anabella (Revista Geográfica de América Central., 2021)
The inclusion of ecosystem services in the planning of urban spaces contributes to mitigating the hydrological impact of urbanization. Under this premise, the objective of the present work was to analyze the regulations associated with the management of stormwater in the capital and provincial capital cities of Argentina, and thus recognize background information regarding the implementation of policies that favor the provision of ecosystem services relevant to the regulation of water resources. Accordingly, zoning ordinances and codes were reviewed. The results obtained were grouped into: urban indicators, zones and green infrastructure measures. Although 87.5% of the considered cities exhibit some type of rule related to ecosystem services pertaining to the regulation of water resources, there is no explicit mention. The above situation makes it difficult to quantify the level of provision of ecosystem services and, therefore, hampers its effective inclusion in urban planning instruments.